SHARED LEADERSHIP UNTUK PENGEMBANGAN SELF-EFFICACY SISWA PADA PEMBELAJARAN KOLABORATIVE BERBASIS CSCL - Putro, Budi Laksono; Nurdyansah, Meggy; Junaeti, Enjun; Putra, Rizky Rachman Judhie; Waslaluddin, Waslaluddin; Rahman, Eka Fitrajaya (Balai Besar Guru Penggerak Jawa Timur, 2023)
Self-efficacy is a person's self-confidence that he is able to overcome a situation based on his abilities. There is evidence that student self-efficacy has an impact on cognitive and metacognitive learning strategies. So students can work harder, and more diligently, increasing their potential and self-esteem. There is still minimal discussion of constructs and indicators that affect the development of student efficacy. The objective of this study is to apply shared leadership to the development of student self-efficacy in computer-assisted collaborative learning (CSCL). Developing a shared leadership for developing student self-efficacy applies the Smart Learning Environment Establishment Guideline (SLEEG) method with a quasi-experimental research plan with one group post-test. The research was conducted at SMK Negeri 13 Bandung with a sample of 32 individuals in class XI TKJ 1. Analysis of research using PLS-SEM with the Smart-PLS application. The results indicate that the shared leadership metric is valid and reliable. Shared leadership has a significant positive impact on self-efficiency, with p-values of 0.049 < 0.05 and 0.013 < 0.5, respectively. It can be concluded that shared leadership in the CSCL environment can create a sense of responsibility for each member of the group and facilitate the process of interaction among students. AbstrakSelf-efficacy atau efikasi diri merupakan keyakinan diri seseorang bahwa dia mampu mengatasi suatu situasi berdasarkan kemampuan yang dia miliki. Self-Efficacy siswa terbukti berpengaruh pada strategi kognitif dan metakognitif dalam pembelajaran. Sehingga siswa mampu bekerja lebih keras, lebih tekun, peningkatan potensi dan kepercayaan diri. Namun demikian masih minim pembahasan konstruk dan indicator yang mempengaruhi pengembangan efikasi siswa. Penelitian ini bertujuan menerapkan shared leadership untuk pengembangan self-efficacy siswa pada pembelajaran kolaborative berbasiskan Computer Supported Collaborative Learning (CSCL). Pengembangan shared leadership untuk pengembangan self-efficacy siswa menerapkan metode Smart Learning Environment Establishment Guideline (SLEEG) dengan desain penelitian quasi experimental dengan one group post-test only. Penelitian dilakukan di SMK Negeri 13 Bandung dengan sampel kelas XI TKJ 1 berjumlah 32 orang. Analisis penelitian menggunakan PLS-SEM dengan aplikasi Smart-PLS. Hasil menunjukan bahwa pengukuran shared leardership valid dan reliabel. Shared Leadership berpengaruh positif signifikan terhadap Self-Efficacy dengan p values masing-masing adalah 0,049 < 0,05 dan 0.013 < 0,5. Dapat ditarik kesimpulan bahwa shared leadership pada lingkungan CSCL dapat melatih rasa tanggung jawab pada setiap anggota kelompok dan memudahkan proses interaksi antar siswa.